A guide to the professional interview : a research-based interview methodology for people who ask questions /: a research-based interview methodology for people who ask questions. (2021) - Løken, Geir-Egil; Bergestuen, Svein Tore, 1974-; Rachlew, Asbjørn
No abstract available